Radiosonde measurements during POLARSTERN cruise PS127 - Schmithüsen, Holger; Otte, Frank; Stöckle, Sonja (Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research, Bremerhaven, 2025)
The meteorological observatory Polarstern continuously performs radiosoundings during times of ship operation. Typically, there is one launch to full altitude at 12 UTC every day. Additionally, there often is a launch with a smaller balloon for forecasting purposes (helicopter operations) around 6 UTC. All data reports are distributed via global networks of the World Meteorological Organisation. All data published here is generally as recorded. Data affected by known technical issues are not contained in this record.
Keywords: Atmospheric soundings; Radiosonde; upper air profiles